Non-Price Criteria for Evaluating Offers in Poland and the European Union - Szymański, Jarosław (Journal of Finance and Financial Law, 2024)
The purpose of the article. An important element that influences the effectiveness of public procurement is the multi-criteria offer evaluation model. Moving away from comparing offers only in terms of their price, a single-criteria model, allows you to choose a more expensive solution, which may turn out to be a cheaper one after many years of use. The impact of non-price criteria also goes beyond quantifiable economic effects and may stimulate pro-ecological and pro-social behavior of entities applying for public procurement. Due to legislative changes in the application of non-price criteria, a study was carried out to determine the preferences of contracting entities from the European Union member states in this respect. The study was extended to identify the types of non-price criteria used by domestic contracting entities.Methodology. Due to the functionality limitations of the European database of tender announcements, part of the work used data from a random sample. Basic statistical measures, estimation and the parametric Student's t-test were used for the analysis.Results of the research. Changes in the structure of the offer evaluation models used were identified and the preferences for using the multi-criteria model were compared between the EU member states whose accession date was before 2004 and others. Statistically significant differences were found in the use of non-price criteria in countries that were incorporated into the EU structures before 2004 and in other countries. The analysis shows that a longer presence in the EU structures increases the use of non-price criteria only in the area of supplies and services. On the domestic market, the change in legislation that took place in 2021 did not eliminate the system pathology consisting in the introduction of dead non-price criteria by contracting entities.